The Reality of Practical Training for the Physical Education Program from the Perspective of Students at Al Al-Bayt University - الشديدة, ميسلون (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
This study aimed to identify the reality of Practical training for the physical education program from the point of view of students at Al Al-Bayt University. The study used the descriptive analytical approach, and to achieve the objectives of the study, the questionnaire was used as a tool to collect data from members of the study sample, which consisted of (63) male and female students in the Department of Physical Education at Al Al-Bayt University. They were selected intentionally from the study population, and after verifying validity and reliability, the study concluded that the reality The Practical training for the physical education program from the point of view of the students at Al Al-Bayt University was highly rated. The results also showed that there were statistically significant differences in the reality of the Practical training for the physical education program from the point of view of the students at Al Al-Bayt University according to the gender of the student teacher in favor of females. No differences appeared according to For the academic year. Based on the results of the study, the researcher recommended. By providing students with educational experiences that keep pace with modern developments, with the need to create an atmosphere and climate of cooperation between supervisors and the school administration with the student teacher.